HUBUNGAN PENGETAHUAN IBU DAN DUKUNGAN SUAMI DENGAN PEMAKAIAN KONTRASEPSI JANGKA PANJANG DI WILAYAH KERJA PUSKESMAS RUMBAI PESISIR - - Nurlisis; Winda Anggraini (LPPM Universitas Muhammadiyah Riau, 2016)
Data from health department pekanbaru city in 2012 from 12.671 kb active participants dikecamatan only 353 (2,78 % one who uses a method of long-term contraception.2011 puskesmas a tassel coastal having the number of 2931 pus , users of a contraceptive method of contraception long-term (mkjp as much as the 564 (19,24 % and a decline in the year 2012 from 8.390 kb active participants using a method of contraception long-term (mkjp) puskesmas a tassel coastal some 261 (3.11 %.This research aims to understand the relation of knowledge mother and husband to support the use of contraceptives long-term work in the region coastal puskesmas tahun2014 a tassel.The type of research is analytic quantitative with the design case control study , conducted from the moon maret- april 2014 with a large sample 50 cases of control and 50.Of all join the who was working diwilyah puskesmas a tassel coastal 2014 which consisted of 261 people. The sample collection technique done simple random sampling.Data processed use a computer program.Using bivariate analysis by this chi squere.The result showed that of the second variables knowledge and support husband has links that are meaningful to discharging long period contraceptives in the work area coastal puskesmas a tassel year 2014 with knowledge p value = 0.02 and support husband value = p.0,001. Recommended to improve health information particularly about the effectiveness and efficiency of a method of contraception long-term (MKJP).